Retzius-Sparing Robot-Assisted Radical Prostatectomy in treatment of prostate cancer – presentation of the method and results - Gorczyca, Przemysław; Bigdoń, Anna Maria; Ćwiek, Maciej; Góra, Mateusz; Hunek, Adrian Krzysztof; Kozłowska, Martyna; Kreft, Rafał; Sydor, Patryk; Wartacz, Marcel; Woźniak, Aleksander (Journal of Education, Health and Sport, 2023)
Background: Prostate cancer is a malignant cancer and the second most frequent malignancy in men. Millions of people are suffering from this problem across the globe. The gold standard for the treatment of this disease is considered radical prostatectomy. This method can lead to a complete cure but is not free of complications. Retzius-sparing modification of robot-assisted radical prostatectomy is a new method that can contribute to better results in faster recovery. Aim of this study: To present the difference between the Retzius-Sparing Robot-Assisted Radical Prostatectomy (RS-RARP) and the Standard Robot-assisted Radical Prostatectomy (S-RARP) in method and results. Materials and methods: A review was conducted in PubMed and Google Scholar including publications from the last 9 years. Literature was searched using the following terms: “Retzius-sparing”, “robot-assisted radical prostatectomy” and “prostate cancer”. Results and conclusion: Retzius-Sparing Robot-Assisted Radical Prostatectomy is a relatively new method that can improve results in prostate cancer treatment. In analyzed original articles RS-RARP compared to s-RARP showed better recovery of continence and lower risk of hernia. Although there were no significant differences in postoperative sexual function, positive surgical margins, and 1-year-biochemical recurrence rate.